A Review on Implementation of Biometric Iris Recognition - Singh, Monika; Sharma, Sanjeev Kumar (International Journal of Computer Sciences and Engineering, 2025)
Biometric is considered as an authentic system to recognize a human with respect to their behavior and body features. Automatic verification of features like finger print, palm print, iris recognition is considered a proficient way to grant an access to any system. Among all those, iris is taken as one of the admired technique of recognition which needs precise recognition to execute the whole system. To extract those features which exists in the texture of eye and identify it with the existing database requires various methods to get performed like segmentation, preprocessing, normalization etc. For all those methods, various algorithms have been developed and their effectiveness varies according to the circumstances in which they have been applied. This paper proposes a review on various systems and their developed technique on which researchers have previously worked. Due to several issues, methods which have been developed, till now, can’t consider for wide implementation. So, the system which has been proposed in this paper provides an iris recognition or authentication system using Savitzky-Golay filter for iris feature extraction. A Savitzky–Golay filter is a digital filter that can be applied to a set of digital data points for the purpose of smoothing or enhancing the data without distorting the information. The approach also proves that the symbolic representation effectively handles noise and degradations, including low resolution, specular reflection, and occlusion of eyelids present in the eye images and uses minimum number of features to represent iris image. This system can be implemented in various fields such as banking, security concern areas and many more. Major Canadian Airports have been using Iris recognition systems to expedite passengers through customs.